Collective redundancies in the State of California of the United States and in the Republic of Finland. Procedures and Provisions - Kopra, Eila (My University, 2015)
Video games industry has recently bonded California and Finland in a new way and where the employers are recruiting they also need to be aware of the provisions and procedures related to terminations. In general, collective dismissals are on a relatively high level both in Finland and in California. In California, collective redundancies are regulated under the WARN law. The WARN obligates employers with 75 or more employees to give a 60-day notice prior to a mass lay off and some other similar events. Employers with less than 75 employees are free to administer the terminations without the WARN notice period. Generally, the California at-will presumption allows employment relationship to be terminated any day with or without reason and without notice period if conditions of collective agreements or employment contract do not limit this right. Termination cannot anyhow be in violation of the anti-discrimination law. In Finland the termination related provisions are part of the Employment Contracts Act and the Act on Co-operation within Undertakings. Collective redundancies are allowed under financial and production related grounds. Small employers with less than 20 employees follow the termination provisions of the Employment Contracts Act and are obligated to inform the employee to be terminated on the details of the termination itself and also the services of the Employment and Economic Development Office. Employers with 20 or more employees are to initiate co-operation procedure under the Act on Co-operation within Undertakings when reducing personnel. The co- operation negotiations are to inform employees on the employer’s plans and financial situation as well as to involve them in the decision making regarding the terminations. The employer’s duty to inform the employees of the services of Employment and Economic Development Office needs to be fulfilled also in terminations under the co-operation procedure. Discrimination is prohibited in Finland in terminations of employment. As an alternative for terminations, employees can for example be transferred to another position or be temporarily laid off. Employer’s duties related to search of alternatives for layoff are broader in Finland than in California. The recent development of the labor laws in Finland and in California suggests that the labor law is not static in either one of these environments but changes can be expected as the needs of the business life so require.